Modified robust external force control with disturbance rejection with application to piezoelectric actuators - Ghafarirad, H.; Rezaei, S.M.; Sarhan, A.A.D.M.; Mardi, N.A. (2015)
In micromanipulation applications, controlling the force exerted on the object is of great importance. In such cases, any uncontrolled forces may damage the object or cause system failure. However, the presence of disturbances such as impedance uncertainties and hysteresis can strongly degrade force control performance and even lead to instability. Therefore, accurate force control when internal and external disturbances occur is a significant challenge. Conventional control methods usually have a number of restrictive conditions especially on the disturbance bounds. To rectify those issues, a modified robust disturbance rejection-based force control approach is proposed in this paper. For this purpose, an appropriate disturbance observer is utilized to estimate the disturbance effect regardless of amplitude. Then a robust control method is employed to achieve the disturbance-free desired dynamic. A modification is also performed to rectify the need for acceleration measurement in the control design. Finally, the force control for an unknown environment in the presence of disturbances is accomplished. The efficiency of the proposed approach is evaluated through simulation studies and compared with the well-known PI method. The experimental results validate the force control performance for the micropositioning piezoelectric actuator.